Distribution in Islam, Contribution of Waqf in Redistribution, and Implementation of Bank Wakaf Mikro - Camelia Rizka Maulida Syukur (Journal of Islamic Economics Lariba, 2019)
The economic disparity caused by the accumulation of wealth in the hands of a group of people can lead to destructive attitudes within a society. Therefore, distribution plays an important role in addressing economic inequality in society. As stated in verse 7 of QS. Al-Hashr, wealth should not circulate only among the rich, as this widens the gap between the rich and poor. Hence, the objective of this research is to analyze the equal distribution of wealth through the instrument of waqf (cash endowment). This is a qualitative study that employs a literature review method, using references from related journals, data from BPS, and some relevant links. The method of interpretation used is maudhu’i interpretation, while hermeneutics is used to understand the meaning of each word contained in the verses being studied. The results of this research indicate that the application of one of the distribution instruments taught by Islam, namely waqf, particularly in the form of cash endowment, is beginning to show results. One example is the presence of Micro Waqf Bank which has been able to improve economic welfare through small and micro businesses. The business model of Bank Wakaf Mikro in eradicating poverty can be summarized in several points, namely: (1) providing financing and mentoring (2) non-deposit taking (3) group-based (4) low-profit sharing, equivalent to 3% (5) without collateral.